1984
DOI: 10.3171/jns.1984.60.5.0985
|View full text |Cite
|
Sign up to set email alerts
|

Estrogen and progesterone receptors in meningiomas

Abstract: Two-thirds of all meningiomas and four-fifths of intraspinal and sphenoidal meningiomas occur in women. Meningiomas frequently enlarge or become symptomatic during pregnancy or during the luteal phase of the menstrual cycle. There is an increased incidence of meningiomas in women with breast carcinoma. In a series of 23 patients with meningiomas, the authors assayed biopsy specimens of the tumor for the presence of estrogen (ER) and progesterone (PR) receptors, using glycerol density gradient centrifugation an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
29
0
5

Year Published

1986
1986
2002
2002

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 125 publications
(35 citation statements)
references
References 36 publications
1
29
0
5
Order By: Relevance
“…In our study of 116 meningiomas, none of them display ER immunoreactivity. On the other hand, we find that the majority of meningiomas is immunoreactive for PR, in agreement with other authors [5][6][7][8]16,17 . The presence of PR and lack of ER has led to believe that these PRs are estrogen independent, unlike PRs present in other hormoneregulated tumors, such as breast and uterus.…”
Section: Discussionsupporting
confidence: 82%
See 3 more Smart Citations
“…In our study of 116 meningiomas, none of them display ER immunoreactivity. On the other hand, we find that the majority of meningiomas is immunoreactive for PR, in agreement with other authors [5][6][7][8]16,17 . The presence of PR and lack of ER has led to believe that these PRs are estrogen independent, unlike PRs present in other hormoneregulated tumors, such as breast and uterus.…”
Section: Discussionsupporting
confidence: 82%
“…It also permits retrospective studies with stored material and the detection of receptors even with small amount of tissue. The ER is undetectable in almost all of studies, using different techniques 6,10,16,17 . It appears that ER is actually devoid in this kind of tumors.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A recent review by Cahill et al found that the results of analysis of steroid hormone receptor in meningiomas fell into two main groups, depending on the presence of clinically important oestrogen receptor. 21 Interestingly, most of the reports describing high concentrations of oestrogen receptor binding in a large proportion of neoplasms originate from France.9122023 Various theories have been put forward to explain this.2123 These include differences in the techniques of tissue biopsy, freezing, duration of storage, and methods of homogenisation. These variables, however, have differed in other reports, which are unanimous in finding low or undetectable concentrations of oestrogen receptor.…”
Section: Calculation Of Receptor Concentrationmentioning
confidence: 99%